A ranking method for prioritising retail store food waste based on monetary and environmental impacts. (10th February 2019) - Dreyer, Heidi C.; Dukovska-Popovska, Iskra; Yu, Quan; Hedenstierna, Carl Philip
Abstract: Food waste has become a major concern globally, leading to high economic, environmental and social awareness, as well as inclusion in international policy documents. In the developed world, the retail stage has the greatest potential for waste reduction as it balances demand with supply, stimulates demand (thus affecting waste at the consumer level) and sets standards to the supply and the products (thus affecting food loss upstream). To precisely direct managerial intervention towards products with high waste-mitigation potential, the waste impact needs to be quantified. Previous studies measuring waste have examined individual metrics exclusive of each other, which affects the ranking of products. The present study proposes a method for prioritising waste based on combined monetary and environmental indicators, and it demonstrates the applicability of the method through empirical data from Scandinavian retail stores. The contribution of the proposed metric is that it results in a unique score comprising economic and environmental impacts for every single product, thus directing the managerial intervention more precisely. In addition, it enables choosing a weight for the economic and the environmental indicators, thus adding to the previous literature that looks at the products either through an economic or environmental perspective, exclusive of each other. Applying the method confirmed the previous research at a product group level that bread, meat and fruits/vegetables are the highest wasters. In addition, for some products, such as meat and fruit, the dependency between economic and environmental impacts is weaker, whereas it is stronger for others (e.g. bread and biscuits), thereby necessitating a method to gauge waste in both dimensions.